2007
DOI: 10.3141/2026-09
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Comparison of Cement- and Bituminous-Stabilized Granular Base Systems

Abstract: The Saskatchewan, Canada, Department of Highways and Transportation is investigating alternative recycling and strengthening systems for inservice thin granular pavements. This research is being performed to improve the granular pavement structural integrity and to reduce the dependence on new source aggregates. A pilot project investigated the mechanistic-climatic laboratory characterization of materials used to construct test sections on Control Section Highway 15-11 (C.S. 15-11). This research demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…It was found that the FASB modulus was temperature sensitive and was also governed more by the confining pressure than the deviatoric stress. Berthelot et al (2001) used triaxial dynamic modulus tests to evaluate different alternative stabilisation methods for a marginal recycled granular base with a high percentage of plastic clay fines. The stabilisation methods included asphalt emulsions and foamed asphalt with and without Portland cement.…”
Section: Stiffnessmentioning
confidence: 99%
“…It was found that the FASB modulus was temperature sensitive and was also governed more by the confining pressure than the deviatoric stress. Berthelot et al (2001) used triaxial dynamic modulus tests to evaluate different alternative stabilisation methods for a marginal recycled granular base with a high percentage of plastic clay fines. The stabilisation methods included asphalt emulsions and foamed asphalt with and without Portland cement.…”
Section: Stiffnessmentioning
confidence: 99%
“…falls short of design expectations (3). Modern field conditions are becoming increasingly challenging for designing road structures and maintaining road networks.…”
mentioning
confidence: 99%
“…Marjerison studied the mechanistic comparison of cement-and bituminous-stabilized granular base systems [17]. Schwartz and Khosravifar studied the design and evaluation of foamed asphalt base materials [18].…”
Section: Introductionmentioning
confidence: 99%